Onderhoud met Edwin Arrison - Helené van Tonder (Acta Theologica)
From text: The thirtieth anniversary of the Kairos document in 2015 served as a stimulus for various events reflecting on this historical document and subsequent movement. Among these were the Kairos 30 conference (Johannesburg on 17-20 August) and a colloquium which reflected on the theme “The challenge of prophetic theology for theology today” (Volmoed, Hermanus, 27-29 September). This interview was conducted in the aftermath of these events with Edwin Arrison. He is the General Secretary of Kairos Southern Africa, a minister of the Anglican Church, and chairperson of the Centre for Christian Spirituality in Cape Town.